Pengaruh Karakteristik Pemerintah Daerah, dan Akuntabilitas terhadap Kinerja Pemerintah Daerah di Sumatera Selatan - Rika Henda Safitri; Umi Kalsum; Trie Sartika Pratiwi (Politeknik Ganesha Medan, 2023)
The purpose of this study is to understand how the proxies for the characteristics of local governments, which consist of the size of the region, the level of regional wealth, the level of regional dependence and capital expenditures can affect the performance of local governments. Then also to understand how accountability can affect local government performance. This study uses the population of all district/city governments in South Sumatra Province for the 2016-2020 fiscal year. The sample used in this study was selected using a purposive sampling method, namely 15 district/city governments with an observation period of five years. The amount of data used in this study is 75 data which is secondary data sourced from the website of the Ministry of Finance, Directorate General of Fiscal Balance. The analysis technique in this study uses panel data regression analysis. By using the help of Eviews. The results of the study explain that the size of the region, the level of regional wealth and capital expenditures have no effect on the performance of the regional government. The level of regional wealth and capital expenditures cannot affect the performance of district/city governments in the province of South Sumatra in 2016-2020. Meanwhile, the level of regional dependence and accountability has a positive influence on the performance of local governments. The level of regional dependence and accountability can improve the performance of district/city local governments in South Sumatra Province in 2016-2020.